PESANTREN TRANSFORMATIF: RESPON PESANTREN TERHADAP PERUBAHAN SOSIAL - Atho Mudzhar (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2008)
The life of the community changes constantly with time. Today there have been changes in various aspects of life. Therefore, Indonesia, Moslems, and Islamic boarding school (pesantren) community all are parts of educational world itself. In this context, it is necessagJo. r pesantren to thing more clearly, more society changes constantly with the twice circle. As a past of national education system, pesantren needy r to be adaptive and accommodative to the process of social change occurred. Pesantren needs to play any constructive role in developing the surrounded community at any aspects of life, both religious aspect and socio cultural and economic aspect. In this context, the article aims at to elaborate on how pesantren should accommodate the recent development without disregarding the predetermined vision and mission.